Quantitative ELISA for SERPINA4/kallistatin - Kurpad Nagaraj Shashidhar; Venkata Lakshmaiah; Chandrappa Muninarayana; Krishna Sumanth Nallagangula (BioTechniques)
Background: SERPINA4/kallistatin is a multifunctional protein expressed from the liver; its concentration in blood circulation reflects the degree of liver dysfunction and may serve as a diagnostic/prognostic biomarker for chronic liver diseases (CLD). Materials & methods: Antibodies specific for SERPINA4/kallistatin were used for the development of an enzyme-linked immunosorbent assay (ELISA). For correlative studies, blood samples from patients with cirrhotic liver and healthy patients were collected from R.L. Jalappa Hospital & Research Centre, Kolar. Results: Interference of other SERPINs was ruled out using western blot analysis. Quantitative ELISA was developed using monospecific antibodies as capture antibodies. Conclusion: The accuracy of the developed ELISA was determined by inter- and intra-assay precision. Linearity was defined using a spiked sample with serial dilutions. Reduced levels of SERPINA4/kallistatin were observed in patients with CLD compared with healthy controls.